OS10.1 Survival analysis of IDH wildtype astrocytomas with molecular features of glioblastoma, WHO grade IV. (6th September 2019) - Tesileanu, C M S; Koekkoek, J A F; Dirven, L; Dubbink, H J; Kros, J M; van Duinen, S G; Smits, M; French, P J; Taphoorn, M J B; van den Bent, M J
Abstract: BACKGROUND: Recently, isocitrate dehydrogenase wildtype (IDHwt) lower grade gliomas (LGGs) that have a telomerase reverse transcriptase (TERT) promoter mutation and/or gain of chromosome 7 combined with loss of chromosome 10 and/or epidermal growth factor receptor amplification have been reclassified as IDHwt astrocytomas with molecular features of glioblastoma, WHO grade IV ('astrocytomas IDHwt, WHO IV'). Survival of these tumors meeting the criteria of these tumors is less well studied. The objective of this study is to compare the overall survival (OS) between the IDHwt astrocytomas, WHO IV and histological glioblastomas (GBMs). MATERIAL AND METHODS: In this retrospective multicenter cohort study, all adult patients with a newly diagnosed IDHwt LGG (histologically WHO grade II or III) and with molecular data available were selected from the Erasmus MC and the LUMC from October 2002 to April 2019. LGG patients showing contrast enhancement with necrosis on the MRI at the time of histological diagnosis were excluded. Molecular data were determined using a diagnostic NGS panel. A historical cohort of 195 patients with IDHwt GBMs with molecular data available was used to compare OS. OS was measured from the date of the first diagnostic MR scan. RESULTS: 79 IDHwt LGG patients were identified of which 62 patients had molecular features of glioblastoma ('astrocytomas IDHwt, WHO IV'), 11 patients did not have these molecular features ('astrocytomas IDHwt, WHO II & III'). In the remaining 6 patients the molecular data were not conclusive (astrocytomas IDHwt, WHO NOS). Patients with astrocytomas IDHwt, WHO IV were slightly older at diagnosis (median age = 57 years) than patients with GBMs IDHwt in the reference cohort or astrocytomas IDHwt, WHO II & III (respectively: median age 55 years, p=0.032 and 47 years, p=0.035). The relatively young age of our GBM IDHwt cohort reflects more extensive molecular testing in younger patients and histologically lower grade tumors. The median OS of astrocytomas IDHwt, WHO IV (23.8 months) was similar to the median OS of GBMs (19.2 months, log-rank test p=0.37). The median OS in 19 patients with only TERT promoter mutations was 16.8 months, similar to GBMs (p=0.94). CONCLUSION: There is no statistically significant difference between the OS of IDHwt astrocytomas with molecular features of glioblastoma and the OS of true glioblastomas. Grade II and III IDHwt astrocytoma with molecular features of glioblastoma should be designated WHO grade IV. The presence of TERT promoter mutations alone in this histological context also qualifies for this designation.